Menjalani Cinta Yang Berlandaskan Kristus: Panduan Alkitabiah Untuk Mencari Pasangan Hidup Di Era Kontemporer - Elfin Warnius Waruwu; Dewita Agresia (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
Living a Christ-based love is a significant challenge in a contemporary era filled with pressures from popular culture and social media influences. This article presents a biblical guide to finding a life partner with strong Christian principles as the foundation. A library study approach is used to scrutinize relevant theological and psychological literature, which provides insight into the biblical principles of love and their application in the modern-day context. Analysis of the literature shows that living a Christ-based love involves being faithful to values such as unconditional love, sacrifice, and commitment to God and each other. However, great challenges arise in maintaining faithfulness to these values amidst cultural influences that call for perfection and self-gratification. In response to these challenges, the practical guidelines resulting from this study emphasize the importance of corporate prayer, shared Bible reading, and openness to receiving the guidance of the Holy Spirit. These steps help couples to strengthen their relationship in Christ, overcome the obstacles they face, and live a love based on the love of Christ with confidence and sincerity.